Allocation of Foreign Aid in a Segmented International Context (The Pakistan Development Review, 1995)
Research on the topic of distribution of foreign aid among recipients is regaining momentum. This is understandable in the light of the knowledge that presently the richest 40 percent of the developing world receives twice as much aid per capita as the poorest 40 percent [UNDP (1994)], while once upon a time foreign aid was sought to accomplish exactly the opposite. The distribution of official development assistance (ODA) is conventionally studied in terms of two models: the ‘recipient needs’ model and the ‘donor interest’ model. In the first, foreign aid flows are seen to satisfy the socio-economic needs of the recipient countries. In the second, national interests of donors, whether these are military, political or commercial, are seen to determine the direction and size of the foreign aid. Empirical studies were made to ascertain and understand whether, on balance, foreign aid is motivated by recipient need or donor interest. There is one class of studies, for example, Mcgillivray (1989), which estimates for donors a compound measure of their allocation bias. The other class of studies, i.e., Maizels and Nissanke (1984) and Grilli and Riess (1992), employs regression analysis to explain allocation of foreign aid by representative variables of recipient need and donor interest.